Physiological Aspects of Legged Terrestrial Locomotion The Motor and the Machine - Cavagna, Giovanni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a succinct but comprehensive description of the mechanics of muscle contraction and legged terrestrial locomotion. It describes on the one hand how the fundamental properties of muscle tissue affect the mechanics of locomotion, and on the other, how the mechanics of locomotion modify the mechanism of muscle operation under different conditions. Further, the book reports on the design and results of experiments conducted with two goals. The first was to describe the physiological function of muscle tissue (which may be considered as the "motor") contracting at a constant length, during shortening, during lengthening, and under a condition that occurs most frequently in the back-and-forth movement of the limbs during locomotion, namely the stretch-shortening cycle of the active muscle. The second objective was to analyze the interaction between the motor and the "machine" (the skeletal lever system) during walking and running in different scenarios with respect to speed, step frequency, body mass, gravity, age, and pathological gait. The book will be of considerable interest to physiology, biology and physics students, and provides researchers with stimuli for further experimental and analytical work.
Experimental procedures in the study of muscular function -- Functional anatomy of muscle -- Measurements made during or starting from a state of isometric contraction -- Measurements made after stretching the contracting muscle -- Muscle thermodynamics -- External, internal and total mechanical work done to maintain locomotion -- Walking -- Bouncing gaits: running, trotting and hopping -- Effect of speed, step frequency, age and gravity on the mechanics of running.
Keywords: Biomedical engineering; Human physiology; Mechanics, Applied; Biophysics; Biomedical Engineering and Bioengineering; Human Physiology; Engineering Mechanics; Biophysics